A study of contemporary Chinese style in Herb display design (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Herb display is the arrangement of herbs in a design setting. A good herb display is crucial in Traditional Chinese Medical (TCM) centres to create a convenient and comfortable physician working environment. The rules of herb display are frequently discussed for medical purposes to enhance work efficiency. However, there is limited research on the application of these rules in interior design, especially for contemporary Chinese TCM stores. This research aims to identify herb display designs in contemporary Chinese-style traditional medical stores and examine how these displays enhance work efficiency. Research data were collected qualitatively through case studies and observations in three TCM stores in Penang, Malaysia. The characteristics and criteria of effective herbs displayed in contemporary Chinese style design were analysed and concluded based on the case studies and observations. The findings indicate that the characteristics of contemporary Chinese herb display design, including spatial design, lighting, colours, materials, and furnishings, significantly contribute to achieving work efficiency in TCM stores. Strategically organizing herb displays can improve workflow, save handling time, and enhance overall efficiency. Furthermore, these displays conserve the cultural heritage of TCM while enhancing workspace accessibility and efficiency.
Keywords: Contemporary Chinese design; Medical displays; Traditional Chinese medicine